Los jóvenes y la educación. Situación actual y cambios intergeneracionales - Rosa María Camarena C. (Universidad Autónoma del Estado de México, 2000)
To be a student is one of the main characteristics that define a stage of life named youth. During the last decades, mexican children have had increasing access to school and remain in it until older ages. It has led to a sustantial raise on young's schooling compared with the past generations, as well as to a close on the educational gender gap it used to exist. Nevertheless, young's levels of school attendance and school attainment are still far from those that would be desirable, and some gender differences still prevail. Using data from the 1997 National Employment Survey and the National Survey on Education, Training and Employment of the same year, this article presents empirical evidence and analizes several topics of the educational situation of today's girls and boys aged 12 to 24 years, such as their school attendance, the educational level they have reached, the age at which they leave school and the type of postsecondary education and career they choice, all of which is compared between girls and boys, as well as between the youngs and their parents.